2023
DOI: 10.1186/s12933-023-02044-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the cumulative exposure to atherogenic index of plasma and ischemic stroke: a retrospective cohort study

Huancong Zheng,
Kuangyi Wu,
Weiqiang Wu
et al.

Abstract: Background Atherogenic index of plasma (AIP) has been demonstrated as a surrogate marker for ischemic stroke, but there is limited evidence for the effect of long-term elevation of AIP on ischemic stroke. Therefore, we aimed to characterize the relationship between cumulative exposure to AIP and the risk of ischemic stroke. Methods A total of 54,123 participants in the Kailuan Study who attended consecutive health examinations in 2006, 2008, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In this study, cumulative AIP was independently positively correlated with CMD, similar to recent research findings. A cohort study involving 54,123 Chinese individuals with an average age of 49.05±11.84 years and a follow-up of 11.3 years found that when the cumulative AIP level was higher than 0.28, the risk of ischemic stroke was 1.45 times higher than when it was lower than -0.50, making cumulative AIP an independent predictor of ischemic stroke [ 24 ]. Data from the China Kailuan study also found that cumulative average AIP was an independent predictor of ischemic and hemorrhagic stroke [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, cumulative AIP was independently positively correlated with CMD, similar to recent research findings. A cohort study involving 54,123 Chinese individuals with an average age of 49.05±11.84 years and a follow-up of 11.3 years found that when the cumulative AIP level was higher than 0.28, the risk of ischemic stroke was 1.45 times higher than when it was lower than -0.50, making cumulative AIP an independent predictor of ischemic stroke [ 24 ]. Data from the China Kailuan study also found that cumulative average AIP was an independent predictor of ischemic and hemorrhagic stroke [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although existing studies have shown a positive relationship between single-time AIP levels and the risk of CMD [ 15 , 22 , 23 ], the relationship between cumulative elevation or improvement of AIP and CMD has not been fully clarified. While a few studies have explored the association between cumulative elevation of AIP and the incidence of new strokes [ 24 ], the impact of AIP changes on CMD requires further validation. Hence, this study aims to assess the impact of AIP changes on the incidence of CMD in middle-aged and elderly Chinese individuals, providing new strategies for the prevention and treatment of CMD in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has explored the association between AIP and cerebrovascular disease, revealing that higher AIP levels are correlated with a higher incidence of atherosclerotic stenosis in the carotid and intracranial arteries [ 10 , 32 ]. In the general population, increased baseline and cumulative AIP levels are associated with a greater risk of ischemic stroke [ 9 , 11 ]. To the best of our knowledge, this study is the first to demonstrate the significant predictive value of baseline AIP level for stroke in individuals with glycemic dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concluded that higher values of AIP can significantly increase the risk of CAD after adjusting for other risk factors [ 6 ]. Moreover, other studies have revealed the prognostic role of AIP in arterial stiffness, atherosclerotic disease, the risk of AMI, ischemic stroke, and MACE [ 7 9 ]. Fu et al demonstrated that diabetic patients with MACE had higher values of AIP, introducing a novel MACE predictor for high-risk patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%